Fecal Calprotectin in Preterm Infants Sepsis with and without Necrotizing Enterocolitis Symptoms - Yani Dewi Suryani; Dwi Prasetyo; Dany Hilmanto (Global Medical & Health Communication (GMHC), 2018)
Necrotizing enterocolitis (NEC) is one of the severe gastrointestinal disorder that predominantly affects preterm infants with high morbidity and mortality. The initial clinical manifestations of NEC are non-specific and indistinguishable from sepsis which making delay in diagnosis. Delayed diagnosis might require surgery and even cause death. Calprotectin is a calcium-binding protein, abundantly present in cytosol fraction of neutrophils, also found in feces, and has been found to increase significantly in gastrointestinal inflammation. This study purpose to compare fecal calprotectin in sepsis preterm infants with symptoms of NEC to sepsis preterm infants without symptoms of NEC. The study was a comparative cross-sectional analytic study performed at the Neonatology ward of Dr. Hasan Sadikin General Hospital Bandung, from October 2013 to January 2014 on 40 sepsis preterm infants aged <28 days. Fecal calprotectin was analyzed using enzyme-linked immunoassay (ELISA) kit. Mann-Whitney U test was used to compare the difference of fecal calprotectin concentration in both groups. There were 20 sepsis preterm infants with symptoms of NEC compared to 20 sepsis infants without abdominal symptoms. The concentration of fecal calprotectin was significantly higher in preterm sepsis infants with symptoms of NEC (790.67 μg/g) than preterm sepsis infants without symptoms of NEC (247.93 μg/g, p=0.019). The increasing of fecal calprotectin might provide relevant clinical information to pediatricians for early warning signs of NEC in preterm sepsis infants. In conclusion, fecal calprotectin in preterm sepsis infants with symptoms of NEC is higher compared to those without abdominal symptoms. CALPROTECTIN FESES PADA BAYI KURANG BULAN SEPSIS DENGAN DAN TANPA GEJALA ENTEROKOLITIS NEKROTIKANSEnterokolitis nekrotikans (EKN) merupakan salah satu gangguan gastrointestinal yang serius terutama pada bayi kurang bulan dengan angka kesakitan dan kematian yang tinggi. Gejala klinis awal EKN yang tidak spesifik dan sulit dibedakan dengan sepsis menyebabkan keterlambatan diagnosis. Keterlambatan diagnosis dapat menyebabkan diperlukan tindakan pembedahan bahkan kematian. Calprotectin merupakan protein yang berikatan dengan kalsium banyak terdapat dalam sitosol neutrofil, dapat ditemukan dalam feses, dan diketahui meningkat signifikan pada keadaan inflamasi gastrointestinal. Penelitian ini bertujuan membandingkan kadar calprotectin feses pada bayi kurang bulan (BKB) sepsis dengan BKB sepsis tanpa gejala EKN. Penelitian ini merupakan penelitian observasional analitik dengan rancangan kasus kontrol yang dilakukan di ruang rawat Neonatologi RSUP Dr. Hasan Sadikin Bandung dari Oktober 2013 sampai Januari 2014 terhadap 40 BKB sepsis berusia <28 hari. Kadar calprotectin feses dianalisis menggunakan kit enzim-linked immunoassay (ELISA). Analisis data menggunakan Mann-Whitney U test untuk membandingkan kadar calprotectin feses antara kedua kelompok. Terdapat 20 BKB sepsis dengan gejala EKN yang dibanding dengan 20 BKB sepsis tanpa gejala EKN. Konsentrasi calprotectin feses pada kelompok BKB sepsis dengan gejala EKN lebih tinggi (790,67 μg/g) secara bermakna dibanding dengan kelompok BKB sepsis tanpa EKN (247,93 μg/g, p=0,019). Peningkatan kadar calprotectin pada feses dapat memberikan informasi klinis bagi dokter sebagai tanda awal EKN pada BKB sepsis. Simpulan, kadar calprotectin feses pada BKB sepsis dengan gejala EKN lebih tinggi dibanding dengan BKB sepsis tanpa gejala EKN.